2007
DOI: 10.1007/s10825-006-0072-z
|View full text |Cite
|
Sign up to set email alerts
|

Electron mobility in silicon and germanium inversion layers: The role of remote phonon scattering

Abstract: We calculate the electron mobility in Si and Ge inversion layers in single-gate metal-oxide-semiconductor field effect transistors. Scattering with bulk phonons, surface roughness and remote phonons is included in the mobility calculations. Various high-κ dielectric materials are considered for both Si and Ge substrates. Overall, Ge outperforms Si, but in general Ge is more affected by the use of high-κ dielectrics. HfO 2 degrades the mobility substantially compared to SiO 2 for Si substrates and may prohibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Hess and Vogl first suggested that remote phonons [sometimes also known as Fuchs-Kliewer (FK) [9] surface optical (SO) phonons] can have a substantial effect on the mobility of Si inversion layer carriers [10]. Fischetti and co-workers later studied the effects of remote phonon scattering in MOS structures and found that high-κ oxide layers have a significant effect on carrier mobility in Si [8] and Ge [11]. This method was later applied by Xiu to study remote phonon scattering in Si nanowires [12].…”
Section: Introductionmentioning
confidence: 99%
“…Hess and Vogl first suggested that remote phonons [sometimes also known as Fuchs-Kliewer (FK) [9] surface optical (SO) phonons] can have a substantial effect on the mobility of Si inversion layer carriers [10]. Fischetti and co-workers later studied the effects of remote phonon scattering in MOS structures and found that high-κ oxide layers have a significant effect on carrier mobility in Si [8] and Ge [11]. This method was later applied by Xiu to study remote phonon scattering in Si nanowires [12].…”
Section: Introductionmentioning
confidence: 99%
“…Vastly superior electron mobility of Si 1−x Ge x on a dielectric substrate is promising use in photonics technologies continue to replace Si-based solid-state electronic devices. Although SiGe can theoretically provide semiconductor devices with better performance than Si-based devices, fabricating high quality SiGe on dielectric substrate is technically challenging due to the lattice constant mismatching between the SiGe and substrate 3–5 .…”
Section: Introductionmentioning
confidence: 99%
“…As V FG is increased, the density in the front channel increases exponentially, whereas the density in the back channel increases more slowly up to V FG ϳ 0.6 V and then saturates, see inset of Fig. 18 This assumed density dependence of mobility, which drops faster than the increase in electron density in the opposite channel, is required to reproduce negative g FG before the front-channel conduction takes over-the front and back channel components of subthreshold I D are indicated in Fig. As the back channel is closer to its threshold, its contribution to I D first increases and then drops due to the mobility degradation of BG .…”
mentioning
confidence: 97%